Fiqh of Bureaucracy and Public Governance in Indonesia: A New Paradigm Based on Maqasid al-Shariah - Ahwadzy, M. Arfan; Baihaqi, Ahmad; Thoha, M.; Muqtafa, Ahmad Rikza; Ainurrofiq, Rusydi; Al Bustomi, Bayazid; Khoirifo, M. (Mafapress - Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) IPMAFA Pati, 2025)
Inefficiency in bureaucracy, corruption, and weak governance are global problems that impact societal welfare. This research introduces fikih birokrasi (bureaucratic jurisprudence) as a new concept that bridges the gap between modern public administration theory and normative Islamic law by using the maqashid syariah (objectives of Islamic law) as its foundational value. The principle of maslahah (public interest) is positioned both as an ethical norm and a practical instrument for creating governance that is just, ssustainable, and accountable. The methodology employed is a descriptive-qualitative approach, utilizing the Miles and Huberman model for analysis. The research findings indicate that fikih birokrasi contributes a practical framework for public administration based on maqashid syariah, which can be operationalized through indicators of Islamic governance. This research presents a discourse offering an alternative paradigm in bureaucracy that connects the worldly-spiritual hereafter dimension, the individual-collective aspect, and material-spiritual needs with the practical demands of modern governance.